Athermal silicon optical interposers with quantum dot lasers operating from 25 to 125°C. Issue 19 (1st September 2014) - Urino, Y.; Hatori, N.; Akagawa, T.; Shimizu, T.; Okano, M.; Ishizaka, M.; Yamamoto, T.; Okayama, H.; Onawa, Y.; Takahashi, H.; Shimura, D.; Yaegashi, H.; et al.
Abstract : Interposers for inter‐chip interconnects should perform stably under high‐temperature conditions and rapid temperature change due to the heat generated by mounted large‐scale integration (LSI) chips. Athermal silicon optical interposers integrated with quantum dot lasers and other temperature‐insensitive components on a single silicon substrate are demonstrated, and error‐free data links at 12.5 Gbit/s operating from 25 to 125°C are achieved without any bias adjustment. Since maximum junction temperatures in most LSIs have been below 125°C now and will be in the future, the interposers are tolerant of heat generated by LSIs, and are suitable for inter‐chip interconnects.